The Role of Cyclooxygenase-1 and -2 in Sevoflurane-Induced Postconditioning Against Myocardial Infarction. (September 2014) - Stumpner, Jan; Tischer-Zeitz, Tobias; Frank, Anja; Lotz, Christopher; Redel, Andreas; Lange, Markus; Kehl, Franz; Roewer, Norbert; Smul, Thorsten
Cyclooxygenase (COX)-2 mediates ischemic pre- and postconditioning as well as anesthetic-induced preconditioning. However, the role of COX-1 and -2 in anesthetic-induced postconditioning has not been investigated. We evaluated the role of COX-1 and -2 in sevoflurane-induced postconditioning in vivo. Pentobarbital-anaesthetized male C57BL/6 mice were subjected to 45 minutes of coronary artery occlusion and 3 hours of reperfusion. Animals received either no intervention, the vehicle dimethyl sulfoxide (DMSO, 10 µL/g intraperitoneally), acetylsalicylic acid (ASA, 5 µg/g intraperitoneally), the selective COX-1 inhibitor SC-560 (10 µg/g intraperitoneally), or the selective COX-2 inhibitor NS-398 (5 µg/g intraperitoneally). 1.0 MAC (minimum alveolar concentration) sevoflurane was administered for 18 minutes during early reperfusion either alone or in combination with ASA, SC-560, and NS-398. Infarct size was determined with triphenyltetrazolium chloride. Statistical analysis was performed using 1-way and 2-way analyses of variance with post hoc Duncan testing. The infarct size in the control group was 44% ± 9%. DMSO (42% ± 7%), ASA (36% ± 6%), and NS-398 (44% ± 18%) had no effect on infarct size. Sevoflurane (17% ± 4%; P < .05) and SC-560 (26% ± 10%; P < .05) significantly reduced the infarct size compared with control condition. Sevoflurane-induced postconditioning was not abolished by ASA (16% ± 5%) and SC-560 (22% ± 4%). NS-398 abolished sevoflurane-induced postconditioning (33% ± 14%). It was concluded that sevoflurane induces postconditioning in mice. Inhibition of COX-1 elicits a myocardial infarct size reduction and does not abolish sevoflurane-induced postconditioning. Blockade of COX-2 abolishes sevoflurane-induced postconditioning. These results indicate that sevoflurane-induced postconditioning is mediated by COX-2.